2017
DOI: 10.4142/jvs.2017.18.4.439
|View full text |Cite
|
Sign up to set email alerts
|

A serine/threonine phosphatase 1 of Streptococcus suis type 2 is an important virulence factor

Abstract: Streptococcus suis is regarded as one of the major pathogens of pigs, and Streptococcus suis type 2 (SS2) is considered a zoonotic bacterium based on its ability to cause meningitis and streptococcal toxic shock-like syndrome in humans. Many bacterial species contain genes encoding serine/threonine protein phosphatases (STPs) responsible for dephosphorylation of their substrates in a single reaction step. This study investigated the role of stp1 in the pathogenesis of SS2. An isogenic stp1 mutant (Δstp1) was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…S. suis 2 utilizes SodA for survival not only by scavenging ROS but also by alleviating the host autophagic responses due to ROS stimulation (Fang et al, 2015 ). The inactivation of a serine/threonine phosphatase (stp1) increases S. suis 2 resistance to oxidative stress and survival in macrophage cells (Fang et al, 2017 ). In the present study, the phosphorylation of SodA was abolished in the stk mutant.…”
Section: Discussionmentioning
confidence: 99%
“…S. suis 2 utilizes SodA for survival not only by scavenging ROS but also by alleviating the host autophagic responses due to ROS stimulation (Fang et al, 2015 ). The inactivation of a serine/threonine phosphatase (stp1) increases S. suis 2 resistance to oxidative stress and survival in macrophage cells (Fang et al, 2017 ). In the present study, the phosphorylation of SodA was abolished in the stk mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Once S. suis reaches deep tissues and/or the bloodstream, phagocytic cells play a pivotal role in the host defense against these invading pathogens during infection (Fang et al, 2017 ). Phagocytosis and intracellular survival assays were performed in RAW264.7 cells to assess the role of SsRex in the context of S. suis –phagocyte interactions.…”
Section: Resultsmentioning
confidence: 99%
“…To deal with these hostile environments, pathogenic bacteria have evolved or acquired regulatory networks to sense and respond to environmental signals by modulating the expression of related genes. In S. suis , the signal regulatory systems contained within the two-component systems (TCSs) such as SalK/R (Li et al, 2008 ), NisKR (Xu et al, 2014 ), CiaRH (Li et al, 2011 ), and SsSTK/SsSTP (Zhu et al, 2011 , 2014 ; Fang et al, 2017 ; Zhang et al, 2017 ), stand-alone regulators (SARs) such as CcpA (Willenborg et al, 2011 , 2014 ) and Rgg (Zheng et al, 2011 ), and other regulators such as CodY (Feng et al, 2016 ), PerR (Zhang et al, 2012 ), AdcR , and Fur (Aranda et al, 2010 ) have been shown to be involved in bacterial metabolism and virulence. To gain further insight into the global regulatory networks of SS2, the role of other uncharacterized regulators should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Copper efflux [20] PmtA Ferrous iron and cobalt efflux, tolerance to hydrogen peroxide-induced oxidative stress [21] MsmK Utilization of multiple carbohydrates, pathogenesis [22,23] Ide Ssuis Degradation of porcine IgM, complement evasion [24][25][26] IgdE Degradation of porcine IgG [27] IgA1 protease/ZmpC Degradation of human IgA1, pathogenesis 1 [28][29][30][31] eSTK Maintaining bacterial morphology, tolerance to stresses, pathogenesis [32][33][34] eSTP Virulence, cell adhesion, and immune evasion 2 [35,36] SspA-1 Virulence, trigger of proinflammatory cytokines [37,38] SspA-2 Pathogenesis, proinflammatory response in macrophages [39][40][41] Superoxide dismutase Oxidative stress resistance, virulence [42,43] NADH oxidase Tolerance to oxidative stress, virulence [44,45] SsnA Degradation of human and porcine neutrophil extracellular traps, pathogenesis [46][47][48] EndAsuis Degradation of neutrophil extracellular traps [49] Enolase Binding of extracellular matrix components, pathogenesis [50][51][52][53][54][55][56][57][58] LuxS Growth, biofilm formation, capsule synthesis, hydrogen peroxide resistance, resistance to fluoroquinolones, pathogenesis [59]…”
Section: Copamentioning
confidence: 99%
“…The role of eSTP in cell adhesion and immune evasion seems to be contradictory between S. suis 2 and 9. Given that eSTP shares high level of homology between S. suis 2 and 9 [ 36 ], further studies should be performed to determine whether the opposite conclusions are attributable to the different serotypes.…”
Section: Eukaryote-like Serine/threonine Kinase and Phosphatasementioning
confidence: 99%